If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = 2x + 44 Reorder the terms: -12 = 44 + 2x Solving -12 = 44 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + -2x = 44 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + -2x = 44 + 0 -12 + -2x = 44 Add '12' to each side of the equation. -12 + 12 + -2x = 44 + 12 Combine like terms: -12 + 12 = 0 0 + -2x = 44 + 12 -2x = 44 + 12 Combine like terms: 44 + 12 = 56 -2x = 56 Divide each side by '-2'. x = -28 Simplifying x = -28
| -8=-(z+5) | | -9z-z=6z-8+6z | | 45=3x-2x-10 | | 8x-5-3x=6x-8 | | 12x-93=5x-9 | | X/4-9=-16 | | Ln(x)+2*x=0 | | 2x+4(x-6)=3(x+2) | | -3(2y+5)+4(3y-6)= | | -8+7+4x=69 | | 7m-25=2n | | 3x^6-24x^3=0 | | 7x-42=2x+38 | | 2z-7z=-z-1-9z | | 4x+9+x=-6 | | 8m-4=8m | | -15x-15=90 | | X-2.16=9.87 | | 12x-12=4+6x | | 3/x=9/25 | | X-9.7=7.8 | | 29,000,000/X=8.57 | | 9z+6z=7z-6+3z | | -3(4t+5)+7(3t-4)= | | -6(3x-4)=120 | | t−8=5(t/3−8 | | 86=x+6x+9 | | 18x+6=2x-9x | | 9x/5-33=3 | | 73=4x+5x+10 | | 6a+18=0 | | x+124=431 |